Report on the damage of three insect species on commercial thornless blackberry (Rubus sp.) in Guilan Province - Reza Hosseini (نامه انجمن حشره‌شناسی ایران)
Farmers in the northern provinces of Iran have recently welcomed thornless blackberry plants. Damaging insect pests of thornless blackberry plants were collected during spring and summer of 2022-2023 in Rasht, Guilan province, Iran. The collected specimens were transferred to the laboratory and identified using taxonomic keys, with the accuracy of the identifications confirmed by the relevant taxonomists. The damage caused by these pests was observed on the fruits, leaves and terminal buds of the stems. Nymphs and adult stages of Peribalus (Peribalus) strictus strictus (Fabricius, 1803) caused the fruits to dry up by feeding on them, Cladius (Priophorus) brullei (Dahlbom, 1835) sawfly larvae fed on blackberry leaves and Dysgonia algira (Linnaeus, 1767) moth larvae damaged the blackberry plants by feeding on the terminal buds of the stems. Notably, Peribalus (Peribalus) strictus strictus (Fabricius, 1803) is reported for the first time from Guilan province. Since these insects may cause significant economic damage in the future, it is essential to conduct further research on them.